The Role of Pelvic Lymphadenectomy in the Management of Prostate and Bladder Cancer - Woods, Michael E. (ScientificWorldJournal, 2007)
A pelvic lymph node dissection is commonly performed by urologists in the surgical management of prostate and bladder cancer. Identification of lymph node metastases provides important prognostic information for both diseases. Despite advances in radiographic imaging, a pelvic lymphadenectomy remains the most accurate method to stage lymph node involvement. In the past two decades, there has been an increase in the diagnosis of early stage prostate cancer, which has led some to omit a pelvic lymphadenectomy in patients thought to have low probability of positive lymph nodes. There is little debate, however, over the inclusion of a lymph node dissection in bladder cancer given the approximately 25% incidence of unsuspected nodal disease at the time of surgery. Controversy exists over the extent of an appropriate lymphadenectomy and its therapeutic efficacy. This review will examine the need, extent, and the potential prognostic and therapeutic benefits of a pelvic lymphadenectomy in prostate and bladder cancer.